Aliens & UFOs 21 famous UFO sightings : with exercises for developing reading comprehension and critical thinking skills - Billings, Henry (Critical reading series, 1999)
Nonfiction articles examining UFO sightings. Each is followed by reading comprehension and critical thinking exercises.